Giant Lipoma Presents from the Buccal Vestibule - Yuki Sakamoto; Gohei Oyama (Case Reports in Dentistry)
A lipoma is a benign tumor, where the parenchyma is composed of adipose tissue. Lipomas comprise 0.1%–5% of all benign tumors in the oral cavity. A 43-year-old man, with a known masticatory disorder, visited the Department of Oral Surgery at our hospital because of a facial swelling. The swelling, which had worsened over 15 years, was not painful, but the patient had discomfort while eating and talking. A detailed examination revealed a smooth, elastic, soft, circular, and yellowish pink pedunculated tumor-like lesion, with a diameter of approximately 40 mm, on the right buccal mucosa. An oval-shaped neoplastic lesion with a well-defined border of 40 mm×20 mm was noted on MRI. Based on these results, the lesion was characterized as being a benign lipoma. The tumor was resected under local anesthesia. The pedunculated tumor was excised with an electric knife, and the wound was sutured. No trismus or paresthesia was noted on the postoperative follow-up.